General Data Protection Law (LGPD) no. 13,709/2018: perception of accounting service providers - Silva, Gabriella Aline Sampaio da; Servilha, Graziele Oliveira Aragão; Santos, Josiane Silva Costa dos; Melo, Sonia Aparecida Beato Ximenes de (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: Research aim was to identify the challenges in the applicability of the General Law for the Protection of Personal Data (LGPD) in accounting service providers in Tangará da Serra/MT. Methodology: This is a descriptive study, with a quali-quantitative approach, classified by the survey technique, with a sample comprised of 33 companies. The data collection instrument used was a questionnaire with closed questions, using the Google Forms tool. Results: The results showed that accounting offices are prepared for the application of the General Data Protection Law, since they consider the consent of the holders essential for the processing of data, informing about the purpose of the data, thus complying with the principles established by law and adopting the necessary measures for data security. The survey revealed financial investment in training, data security systems and qualified professionals. Contributions of the Study: The research contributes in a practical way by presenting how accounting firms are adapting to the General Data Protection Law, identifying the implementations and procedures necessary to comply with the law.